Preferences for and acceptability of long-acting HIV prevention products among pregnant and lactating women accessing health services in Kenya: a mixed method cross-sectional analysis - Vallery Ogello; Paul Mwangi; Zachary Kwena; Nicholas Thuo; Catherine Makokha; Emmah Owidi; Nelson Muteti; Catherine Kiptinness; Nelly R. Mugo; Kenneth Ngure (BMC Infectious Diseases)
Abstract Background Increased risk of HIV acquisition during pregnancy and lactation among women is evident, necessitating their inclusion in the evaluation of new HIV prevention interventions. Pregnant and postpartum women specifically face challenges with oral PrEP associated with stigma, and the burden of using other tablets. Long-acting products may address challenges related to oral PrEP, however, there is limited data on product-specific preferences and acceptability among pregnant and lactating women. Methods We conducted a mixed-method study to assess the preferences and acceptability of long-acting PrEP modalities either under development or already established among pregnant and lactating women. We conducted quantitative surveys (n = 434) and in-depth interviews (n = 80) in central and western Kenya. We used descriptive statistics and categorical variables to summarize frequencies and proportions. Inductive and deductive content analytic approaches were used for in-depth interviews. Results The median age of respondents was 25 years (IQR 19.3–31.0). Majority were married (263/434, 61%), had completed high school (222/434, 51%), with no condoms use in the prior 3 months (348/434, 80%). The most preferred PrEP formulations were injectable (251/434, 57%) and implantable (175/434, 40%) options. Participants who preferred injectable PrEP had 8.56 times higher odds of considering ease of use as a reason. (aOR = 8.56, 95% CI [3.81–20.48]) and 3.71 odds of choosing perceived discreteness (aOR = 3.71, 95% CI (1.57–9.97)) as their preference reasons. Participants who preferred Implant for HIV prevention had 2.31 odds of considering it due to perceived effectiveness in preventing HIV as a preference reason (aOR = 2.31, 95% CI (1.21—4.66)) and 2.53-fold of considering discreteness as a preference reason (aOR = 2.53, 95% CI (1.46—4.59)). From the in-depth interviews, women reported prospective acceptability due to the perceived convenience of LA products, perceived effectiveness, reduced cost, improved privacy, and reduced stigma. Women had concerns regarding the safety and efficacy of the products during pregnancy and lactation. Conclusion Acceptability of LA products underscores the importance of considering the unique needs of pregnant and breastfeeding women in the development of future prevention interventions. Aligning preferences and needs would enhance the uptake and adherence outcomes of HIV prevention products.